Bioactives and exercise synergize to modulate AMPK and inflammation - Sheng, ZhaoHui; Luo, Quan; Liu, XianChu; Yang, Xingjie (Frontiers in Immunology, 2026)
AMP-activated protein kinase (AMPK) regulates energy homeostasis and immune responses, making it a key target for immunometabolic disorders like obesity, insulin resistance, and neurodegenerative diseases. This review explores the synergistic effects of plant-derived bioactives (e.g., quercetin, resveratrol, curcumin) and exercise on AMPK signaling, focusing on metabolic and immunological outcomes. A systematic search (PubMed, Scopus, Web of Science, up to June 2025) identified 14 preclinical studies showing that combined interventions enhance AMPK phosphorylation, mitochondrial biogenesis, glucose uptake, and lipid oxidation while reducing pro-inflammatory cytokines (e.g., TNF-α, IL-6) and NF-κB signaling via SIRT1/PGC-1α/Nrf2 pathways. Tissue-specific effects in skeletal muscle, heart, brain, liver, and adipose tissue highlight their therapeutic potential. Variability in study designs and limited clinical data necessitate further mechanistic studies, particularly on epigenetic regulation (e.g., histone acetylation, miRNAs), to optimize personalized non-pharmacological strategies.